Perawatan saluran akar periodontitis apikalis kronis pada gigi insisivus lateral maksilaris kiri - Stefani, Rosita (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Root canal treatment is one of the modalities to treat periapical lesions. The success of root canal treatment in periapical lesions can be seen with the patient's chief complaint and the healing of periapical lesions as seen by the radiograph. Objective: This case report aims to demonstrate root canal treatment on a maxillary anterior tooth with periapical lesion. Case report: A 22-year-old female patient came with complaints of a maxillary anterior tooth that had throbbing pain several months ago, after having it filled by a previous dentist, and since then, it has never hurt again. Intra-oral examination of tooth 12 showed composite resin on the mesiopalatal surface. Radiographic findings showed that there was a round radiolucency in the periapical area with a diameter of 4 mm. Root canal treatment was performed based on the diagnosis of chronic apical periodontitis et causa necrotic pulp. Root canal treatment begins with the application of a rubber dam, opens the cavity, explores the root canal, and shapes the root canal. Biomechanical preparation was carried out using Protaper Hand Use with crown down technique, combined with 2.5% NaOCl irrigation. The first visit ends with the disinfection of the root canal using calcium hydroxide. Subsequent treatment was carried out with subjective and objective examination, removal of temporary filling, cleaning of calcium hydroxide, and final irrigation with 2.5% NaOCl, 17% EDTA, and 2% CHX. Obturation was achieved using the vertical condensation technique. The restoration was accomplished at the next visit using composite resin. Conclusion: Root canal treatment on teeth with chronic apical periodontitis was successfully carried out.